Fungal Biomass Responses in Oil Perturbated Tundra at Barrow, Alaska - Miller, Jr., O.K.; Linkins, A.E.; Chmielewski, M.A. (ARCTIC, 1978)
The effects of two Prudhoe Bay crude oil treatments of 5 and 12 l/square m on fungal hyphae/gm dry wt of soil and on the grams of mycelium/square m were followed in polygonal tundra for three seasons. A significant depressing effect of oil on fungal hyphae was evident over three seasons. However, no significant difference between oil treatments was recorded. The moisture content of the soil appeared to influence the mobility of the oil. Shifts occur in fungal populations in the presence of oil and the presence of oil biodegradation by filamentous fungi was detected. The influence of bulk density on fungal populations and the penetration of oil into tundra soil is discussed.